Descompuneti in factori : x^3-27 ; 8x^3+1

Răspuns :

Explicație pas cu pas:

[tex] {x}^{3} - {3}^{3} = (x - 3)( {x}^{2} + 3x + 9) [/tex]

[tex] {(2x)}^{3} + 1 = (2x + 1)( {4x}^{2} - 2 + 1)[/tex]

Răspuns:

x^3 - 27 = (x^2 + 3x + 9)(x - 3)

8x^3 + 1 = (4x^2 + 2x  + 1)(2x - 1)

Explicație pas cu pas:

x^3 - 27 =

x^3 + 3x^2 + 9x - 3x^2 - 9x - 27  =

x^3 + 3x^2 + 9x - 3x^3 - 9x - 27 =

x(x^2 + 3x + 9) - 3(x^3 + 3x = 9) =

(x^2 + 3x + 9)(x - 3)

8x^3 + 1 =

8x^3 - 4x^2 + 2x + 4x^2 - 2x + 1 =

8x^3 - 4x^2 + 2x + 4x^2 - 2x - 1 =

2x (4x^2- 2x + 1) - (4x^2 + 2x + 1) =

(4x^2 + 2x  + 1)(2x - 1)